Use of Mobile Technologies in the Process of Information Technologies Training in the Secondary School - Kateryna Osadcha; Angelica Babich (Ukrainian Journal of Educational Studies and Information Technology, 2017)
The article actualizes the problem of improving the process of teaching informatics in a secondary comprehensive school. It was noted that the technology of using mobile learning tools was covered by scientists J. Attewell, K. L. Buhaichuk, I. O. Zolotareva, V. V. Osadchyi, D. L. Revenaugh, A. M. Trush and others. V. O. Kuklev, Ye. D. Patrakin, A. A. Fedosieiev, B. Banister and others highlighted prospects and possibilities of mobile learning in their works. M. Yu. Novikov raised the question of possibility to use mobile technologies in the school curriculum of informatics in senior classes. However, the use of mobile technologies by secondary school students while studying informatics has been hardly covered in home researches.